The Role of The Surrounding Environment as A Learning Source on Learning Outcomes of Class XI Students in SMAN 1 Polanharjo Klaten - Azimah, Rizki Nor; Wardhani, Puspita Indra (Jurnal Pendidikan Ilmu Sosial, 2022)
The purpose of this study was to determine the learning outcomes of class XI students at SMA Negeri 1 Polanharjo in the subject of geography by using the surrounding environment as a learning resource. The research method used is descriptive quantitative research with a correlation research design. Data collection techniques using interviews and questionnaires. Interview data was conducted with the teacher while the questionnaire data was carried out on students with the number of respondents being 60 students from 4 classes. To test the role of the surrounding environment on student learning outcomes used analytical techniques using product moment correlation. The results showed that the learning outcomes of class XI IPS students at SMA Negeri 1 Polanharjo, Klaten Regency, showed significant results, namely 0.329, the value had a positive value with a strong degree of relationship.